Qualitative Evaluation of Computer-Aided Teleopearation - Al-Mouhamed, M. (2020)
Abstract—Computer-aided teleoperation (CAT) is investigated for extending human eye-hand motion coordination and dexterity. A telerobotic system consisting of a master arm and a slave arm interconnected by a computer network is designed. The proposed system is evaluated using a set of experiments which are (1) operating drawers, (2) pouring of water, and (3) wirewrapping. The non deterministic behavior of force contact favor a qualitative evaluation of teleoperation methodology. Direct teleoperation is evaluated using following schemes: (1) direct bilateral master-slave (DBMS) with stereo vision, (2) DBMS with vision and force feedback, and (3) BDMS with vision and active compliance. CAT tools used are space indexing, scalability, and selective scalability (blocking). Stereo vision is critical resource for teleoperation even with highly coordinated tool motion but it is not efficient alone to avoid excessive contact force and to shorten task time. Slave compliance continuously searches to nullify the external forces by correcting the tool position and orientation based on measured contact force. Space indexing is essential to maintain tele-operation in operator dexterity. Selective scalability is frequently used to linearly block some motion directions while keeping other directions under direct operator control. Mapping of operator hand motion and force to a dynamically computed tool point proved to reduce operator’s cognitive load and task time and ease of understanding of force feedback. This greatly reduces the number of task iterations because the tool DOFs become decoupled, i.e. varying one likely not to affect the others.